Initial model testing of a cantilever beam - SKRODZKA, E.; HOJAN, E. (Archives of Acoustics, 1994)
This paper is devoted to modal testing and to the problem of contactless measurements of a system response signal. The aim of investigation was to establish the best, contact less method for obtaining experimental data used in the process of modal analysis of vibrating objects. Measurements were carried out for a cantilever beam. The beam was excited manually by a small/large impact hammer with a force transducer. The response signal was measured by a microphone probe and a condenser microphone. For comparison, the response signal was also measured by an accelerometer. The spectra of both the exciting and the response signals were delivered to a dual channel analyzer from which the Frequency Response Function (FRF) was obtained. On the basis of FRFs, modal parameters (modal frequencies and mode shapes) were established. A comparison was made between experimental results and theoretical calculations.